Sports Injuries and Prevention - Kanosue, Kazuyuki; Ogawa, Tetsuya; Fukano, Mako; Fukubayashi, Toru (Springer Japan : Imprint: Springer, 2015)
This book presents the incidence of sports-related injuries, the types of injuries specific to particular sports, and the importance of factors such as age and gender. Possible injury mechanisms and risk factors are presented based on an analysis involving recent scientific findings. A variety of sports are included to allow the reader to better generalize the results as well as to apply appropriate procedures to specific sports. The authors have emphasized basic scientific findings to help the reader gain a broad knowledge of sports injuries. The potential audience includes medical doctors, physical therapists, athletic trainers, coaches, and interested parents. This book is expected to play a prominent role in the construction of training programs for both healthy and injured players. The focus on junior athletes will aid in their education, injury prevention, and increased performance. It will also benefit instructors at the junior and senior high school levels. The book is composed of seven parts. In the beginning part, current situations and the general characteristics of sports-related injuries are outlined on the basis of an investigation utilizing statistical data involving a large number of populations. In the following parts, detailed information on the injuries in terms of the types of sports activities, body sites, symptoms, and the relationships among these factors are discussed. Part 2, for example, deals with topics on concussion and severe head-neck injuries which occur frequently in rugby and judo. In Parts 3 and 4, as one of the major sports-related injuries, anterior cruciate ligament (ACL) injuries are discussed. Beginning with the underlying mechanisms as assessed by using the latest measuring techniques, characteristic features of their occurrence are described. Further, Part 4 deals with topics on post-operative (ACL reconstruction) aspects of ACL injuries, especially those related to muscle functions and tendon regeneration in the hamstring muscles. Part 5 deals with muscle strain and focuses particularly on those occurring in the hamstring muscles, as this muscle group is known, as one of the most frequent sites of muscle strain. In Part 6, disorders related to the ankle and foot are introduced. Finally, Part 7 provides information on lower back disorders. Included are detailed mechanisms of their incidence, epidemiology, and implications for their prevention.